The effect of implementing environmental disclosure in Manufacturing Companies - Syalia Masarrah; Mirna Nisfaul Laili; Avi Sunani; Ulfa Puspa W. Widodo; Muh. Syah Arief A. Wijaya (Future Science, 2023)
Environmental disclosure is a useful tool for evaluating a company's environmental performance. Environmental performance is impacted by environmental disclosure. Information on the environment that is included in the company's annual report is also considered environmental disclosure. The financial statements of the company, performance reports, and information about the company's capital or share circulation are just a few of the sources or supporting resources that are required to bolster this review. This study's methodology is a literature review that draws on qualitative data from 15 worldwide journals or papers. The findings demonstrate that, depending on which areas are benefited and which are not, environmental performance can have a favorable or negative impact on the business. However, if disclosure is given, it will indicate the general state of the business, whether it is doing well or not. Investor trust may be lowered and the company's reputation may suffer if there are instances of abnormal behavior. Because of this, experts advise businesses to enhance their corporate culture, rules, and procedures prior to disclosing any environmental information.